2022
DOI: 10.3390/ijerph191912357
|View full text |Cite
|
Sign up to set email alerts
|

Gender Transformative Interventions for Perinatal Mental Health in Low and Middle Income Countries—A Scoping Review

Abstract: Perinatal mental health problems are linked to poor outcomes for mothers, babies and families. In the context of Low and Middle Income Countries (LMIC), a leading risk factor is gender disparity. Addressing gender disparity, by involving fathers, mothers in law and other family members can significantly improve perinatal and maternal healthcare, including risk factors for poor perinatal mental health such as domestic violence and poor social support. This highlights the need to develop and implement gender-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Studies from high-income contexts, such as the United States and Denmark, have highlighted that contemporary families in these settings have moved away from traditional gender roles and towards equal distribution of childcare and paid workforce participation ( Bianchi et al, 2012 ; Gracia and Esping-Andersen, 2015 ; McGill, 2014 ). Globally, studies have demonstrated that gender inequitable attitudes towards parenting and women’s engagement in income-generating work are harmful for both the mother and the child ( Ewerling et al, 2020 ; Raghavan et al, 2022 ). For example, a study using data from 122 countries found that gender inequality was significantly correlated with gender disparities in depressive disorders, suggesting women’s mental wellbeing is strongly impacted by inequalities at the societal level ( Yu, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from high-income contexts, such as the United States and Denmark, have highlighted that contemporary families in these settings have moved away from traditional gender roles and towards equal distribution of childcare and paid workforce participation ( Bianchi et al, 2012 ; Gracia and Esping-Andersen, 2015 ; McGill, 2014 ). Globally, studies have demonstrated that gender inequitable attitudes towards parenting and women’s engagement in income-generating work are harmful for both the mother and the child ( Ewerling et al, 2020 ; Raghavan et al, 2022 ). For example, a study using data from 122 countries found that gender inequality was significantly correlated with gender disparities in depressive disorders, suggesting women’s mental wellbeing is strongly impacted by inequalities at the societal level ( Yu, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Programs leveraging normative ideals (e.g., strength, willpower, provider) may successfully ''engage men'' but may not allow for the challenging of harmful gender norms or unequal power relations. For example, many programs designed to engage fathers and husbands in maternal and perinatal health care have appeared superficially positive, but may inadvertently cause power imbalance and gender disparities when the focus of program content leads men to assume the stance of ''protecting'' and ''looking after'' women (Raghavan et al, 2022).…”
Section: Contentmentioning
confidence: 99%
“…In practice, this means developers considering a range of content that will help work toward structural and community-level changes in behaviors and attitudes, such as institutional policies specific to the context in which individual choices are enacted (e.g., workplaces), rather than solely focusing on the individual ( Dworkin et al, 2015 ). Drawing again from the lessons of fatherhood programs, targeting health provider policy to enhance men’s engagement in routine maternal health care has been noted to achieve sustained change promoting gender equality (e.g., protecting women, families and children from violence), and not solely activities that focus on individual fathers’ attitudes toward gender norms and fatherhood ( Raghavan et al, 2022 ). Mechanisms for supporting structural and community-level change are nascent and we echo calls for developers to implement rigorous evaluations of gender-transformative programs to help generate evidence to guide the future work of others on ways to scale up promising approaches ( Dworkin et al, 2015 ).…”
Section: The 5c Frameworkmentioning
confidence: 99%
“…Additionally, equipping providers with the basic knowledge and skills in gender transformative care, trauma-informed care, and mental health and counseling can help them to prevent, identify, address, and/or refer mental health issues in the perinatal period. Community assets should be leveraged so the wisdom and experience of community leaders, elders, and peers can offer a wider network of informed, compassionate support that helps to shift the stigmatizing norms and expectations of how a mother should feel or react after birth [ 24 ]. We can take the mental health needs of providers seriously by managing their psychological risks; protecting and promoting their mental health through training, skills building, and empowerment; and supporting those with mental health conditions per guidance from the International Labour Organization [ 25 ].…”
mentioning
confidence: 99%